"You can't break…when you're already broken": The importance of school climate to suicidality among LGBTQ youth. Issue 3 (2nd July 2016) - Peter, Tracey; Taylor, Catherine; Campbell, Christopher
ABSTRACT: Suicide has been a longstanding problem among sexual and gender minority youth in Canada. The goal of the article is to examine the link between suicidality and school climate within a theoretically informed framework and a mixed methods approach. Qualitative and quantitative findings are presented using data from more than 3, 700 secondary students from the National Climate Survey of Homophobia and Transphobia in Canadian Schools (Taylor & Peter, 2011a). The findings show that even modest efforts to shift the balance of heteronormative discourse on behalf of lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) students can have profound effects on the experiences and perceptions of sexual and gender minority youth, which we argue would go a long way in reducing incidents of suicidality among LGBTQ youth. In many jurisdictions across Canada, LGBTQ-inclusive policies have attempted to improve school climates and reduce the effects of homophobia and transphobia in schools. These initiatives, along with the work done by Egale Canada to create a National Youth Suicide Prevention Strategy, are important steps in addressing the needs of LGBTQ youth.